Operation Standard for Sling Exercise with Tuina Therapy of Traditional Chinese Medicine Rehabilitation Techniques - LI Li; CHANG Guangzhe; SUN Guodong; SUN Jinglong; FENG Ziyun; MA Zhaoshui; CHENG Yiran (康复学报)
The technique of sling exercise with Tuina therapy is a rehabilitation technique that combines traditional Chinese medicine and Western medicine. It integrates traditional Chinese medicine massage and suspension exercise training to treat motor dysfunction with the help of sling training system based on the theory of meridians and collaterals in traditional Chinese medicine, modern biomechanical fascia theory and neurodevelopment theory. The main purpose of establishing the operation standard of "technique of sling exercise with Tuina therapy" is to standardize the management and guidance of traditional Chinese medicine doctors, rehabilitation therapists and other professional and technical personnel to correctly applye the "technique of sling exercise with Tuina therapy" for rehabilitation treatment. This scientific, standardized and unified operation technical standard covers the scope of practice, normative reference documents, terms and definitions (recipient, performer, sling training, exercise techniques, massage, technique of sling exercise with Tuina therapy, weak link, meridians, twelve meridians and collaterals, tendons, twelve cutaneous regions, governor vessel, belt vessel, three hand yang meridians, three hand yin meridians, three foot yang meridian, three foot yin meridians), indications, contraindications, functional evaluation (basic requirements, pain assessment, motor function evaluation), operation steps and requirements ［preparation before operation (environmental requirements, tool preparation, performer preparation ), operation process (positioning weak link meridians, selecting sling position, sling Tuina treatment, sling exercise training, relaxation, precautions, treatment course )］, curative effect evaluation, etc. This technical specification can provide operational guidance for traditional Chinese medicine doctors, rehabilitation therapists and other professional and technical personnel to perform "technique of sling exercise with Tuina therapy" rehabilitation treatment, with good clinical applicability, safety and effectiveness.